Effect of Exercise-Induced Enhancement of the Leg-Extensor Muscle-Tendon Unit Capacities on Ambulatory Mechanics and Knee Osteoarthritis Markers in the Elderly - Karamanidis, Kiros (Public Library of Science, 2014)
OBJECTIVE: Leg-extensor muscle weakness could be a key component in knee joint degeneration in the elderly because it may result in altered muscular control during locomotion influencing the mechanical environment within the joint. This work aimed to examine whether an exercise-induced enhancement of the triceps surae (TS) and quadriceps femoris (QF) muscle-tendon unit (MTU) capacities would affect mechanical and biological markers for knee osteoarthritis in the elderly. METHODS: Twelve older women completed a 14-week TS and QF MTU exercise intervention, which had already been established as increasing muscle strength and tendon stiffness. Locomotion mechanics and serum cartilage oligomeric matrix protein (COMP) levels were examined during incline walking. MTU mechanical properties were assessed using simultaneously ultrasonography and dynamometry. RESULTS: Post exercise intervention, the elderly had higher TS and QF contractile strength and tendon-aponeurosis stiffness. Regarding the incline gait task, the subjects demonstrated a lower external knee adduction moment and lower knee adduction angular impulse during the stance phase post-intervention. Furthermore, post-intervention compared to pre-intervention, the elderly showed lower external hip adduction moment, but revealed higher plantarflexion pushoff moment. The changes in the external knee adduction moment were significantly correlated with the improvement in ankle pushoff function. Serum COMP concentration increased in response to the 0.5-h incline walking exercise with no differences in the magnitude of increment between pre- and post-intervention. CONCLUSIONS: This work emphasizes the important role played by the ankle pushoff function in knee joint mechanical loading during locomotion, and may justify the inclusion of the TS MTU in prevention programs aiming to positively influence specific mechanical markers for knee osteoarthritis in the elderly. However, the study was unable to show that COMP is amenable to change in the elderly following a 14-week exercise intervention and, therefore, the physiological benefit of improved muscle function for knee cartilage requires further investigation.